2021
DOI: 10.26418/ja.v2i2.51660
|View full text |Cite
|
Sign up to set email alerts
|

Cover, Daftar Isi, Isi

Abstract: VOl 2 No 2 Desember 2021

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…However, with time, peroxide values in cookies premix increased gradually, ranging from 0.96 to 2.96 meq/kg during the 30-90 days of storage period. Despite this, the peroxide values remained within the permissible limit of 10 meq/kg of extracted fat [37] even after three months of storage. The increase in peroxide values during storage is due to the degradationof fat and the oxidation of fat which leads to the formation of peroxides.…”
Section: Peroxide Value (Pv)mentioning
confidence: 85%
“…However, with time, peroxide values in cookies premix increased gradually, ranging from 0.96 to 2.96 meq/kg during the 30-90 days of storage period. Despite this, the peroxide values remained within the permissible limit of 10 meq/kg of extracted fat [37] even after three months of storage. The increase in peroxide values during storage is due to the degradationof fat and the oxidation of fat which leads to the formation of peroxides.…”
Section: Peroxide Value (Pv)mentioning
confidence: 85%
“…The data in Tables 5 and 6 showed that the available soil contents of heavy metals did not exceed the permissible limits at two study seasons according to Kabata-Pendias and Pendias. (1992), ISI (1983) EUS (2002), except for Pb in tow sites at winter season were No. 7 and 8 with values of 1.1, 1.03 mg kg -1 (Fig.…”
Section: -Effect Of Using Low-quality Irrigation Water From El-mentioning
confidence: 97%
“…Pb caused neurological and behavioral effects such as sub-encephalopathy and was toxic to the central and peripheral nervous systems. Its excessive consumption may eventually be fatal and cause hearing loss, blood disorders, and hypertension (ISI 1991;WHO 1993).…”
Section: Trace Element Distributionmentioning
confidence: 99%